PERCEPTIONS OF TECHNICAL AND SOCIAL PRESENCE TOWARDS CUSTOMERS TRUST AND VALUE: CLICK-AND-BRICK VERSUS PURE-CLICK RETAILERS - Kurniawan, Joshua Jeffrey; Achyar, Adrian (ASEAN Marketing Journal, 2021)
Manuscript type: EmpiricalResearch Aims: Sellers/retailers understand that there is always a risk behind online interaction (e.g., anonymity or proximity) and respond with the multi-platform commercial channel (click-and-brick). Consequently, the click-and-brick (multi-channel) retailers gain, relatively, an immense prominence and rivalry from the pure-click (single-channel) retailers. The present study attempts to measure the impacts of both retailers’ (multi and single) web-features on trust and value perceptions.Design: Utilising structural equation modelling, the current study recruited 565 experienced respondents to provide primary data.Research Findings: These empirical findings provide several insights (recommendations) to pureclick retailers in developing and promoting offline presence, thus weathering the competition from multi-channel retailers.Theoretical Contribution: Past authors propose online loyalty construct into the online consumer behaviour. However, they ultimately concluded that the employed e-service features produced insignificant influence on the patron’s e-loyalty. Instead of the e-loyalty variable, the perceived value construct is introduced in the recent study.Research Limitation: Limitation of the present study originates from the research scope, whichrevolves around customer’s perception of a real-life retailer’s brand. The question remains if the retailer’s unresolved negative performance could overwrite the perceived value and make them prone to brand-switching.